O ensino de física no ensino remoto emergencial: possibilidades e desafios - Goulart, Bruna Natiele Kemerich (2023)
Education experienced an atypical scenario during the Covid-19 pandemic, from the beginning of 2020 in Brazil. Social distancing measure was proposed to contain the spread of the virus and, in education, it led to the closure of schools and implementation of emergency remote teaching (ERT). In this process, Digital Information and Communication Technologies (DICT) had great prominence due to the incorporation of technological tools by teachers and students in the teaching-learning proces. Thus, with this research, we seek to understand the relationships between educational practices and DICT, mainly in the context of the development of the work of Physics teachers in the ERT. Faced with this reality, this research seek to answer the following problem: What challenges and possibilities can be perceived in the organization and development of the teaching work of Physics teachers in the ERT, in high schools in São BorjaRS? Located in the fields of research in Education and Teaching, it takes as its object of study the teaching and learning processes of Physics within the context of emergency remote teaching. Data collection on the ERE was carried out with professors who teach Physics at state basic education schools in the municipality of São Borja-RS. This search for answers about emergency remote teaching consisted of a questionnaire and individual interviews with teachers. Data analysis took place through Discursive Textual Analysis (DTA), which is a mediating tool in the production of meanings, produced through the interpretation and production of arguments. With the pandemic, a series of problems and difficulties directly impacted education, such as the lack of preparation of teachers to deal with DICT, access to the internet by students, emotional issues, in addition to socioeconomic aspects. Some results point to the need for better pedagogical training for the use of DICT in Physics teaching, which is why it is important for teachers to critically and creatively appropriate DICT in teaching physical concepts. In our analysis, it was possible to perceive the need for continuing education for teachers, especially in relation to the incorporation of DICT into the teaching of Physics in basic education. It is considered that the insertion of DICT in the teaching of Physics is fundamental, considering the need to make teaching more playful and critical, given the new faces produced by technological advances. Linked to teaching-learning, the need for continued training of teachers with an emphasis on DICT.